2014
DOI: 10.3329/jles.v8i0.20134
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activities of Abroma Augusta (L.) Chloroform and Methanol Extracts Against Tribolium Castaneum (Herbst) Adults

Abstract: The chloroform and methanol extracts of the leaves, root wood, stem bark, stem wood and seeds of Abroma augusta (L.) (Ulatkambal) were tested against Tribolium castaneum (Herbst) adults through residual film assay. The seed extracts (CHcl3 and MeOH) were found to offer the highest mortality of the beetles and the LD50 values were 3046.083, 247.9217 and 75.96001 ?g/cm2 and 6598.793, 340.4855 and 113.6461 ?g/cm2 for the (CHCl350 values of 1127.785, 312.5822 and 146.3708 ?g/cm2 and 1689.468, 449.8259 and 134.9692… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…From this result, R. communis showed a more effective value than A. augusta extracts because after 72 h of administration, 100% borer were controlled by 50% R. communis where 100% A. augusta extract was used. Previously, chloroform extracts of A. augusta seed, root wood, leaves, and stem bark showed repellent efficacy against adult Tribolium castaneum beetles at dose levels of 314.540, 157.270, 78.635, 39.318, 19.659, and 9.831 g/cm 2 on filter paper (Mondal et al, 2013). A. augusta is also used for stomachaches, diabetes, dermatitis, and as an abortifacient and anti-fertility agent in powdered form.…”
Section: Discussionmentioning
confidence: 99%
“…From this result, R. communis showed a more effective value than A. augusta extracts because after 72 h of administration, 100% borer were controlled by 50% R. communis where 100% A. augusta extract was used. Previously, chloroform extracts of A. augusta seed, root wood, leaves, and stem bark showed repellent efficacy against adult Tribolium castaneum beetles at dose levels of 314.540, 157.270, 78.635, 39.318, 19.659, and 9.831 g/cm 2 on filter paper (Mondal et al, 2013). A. augusta is also used for stomachaches, diabetes, dermatitis, and as an abortifacient and anti-fertility agent in powdered form.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various studies have demonstrated the insecticidal activities of chloroform extract against pests from other plants such as shrubby whilevein, Sanchezia speciosa Hook. F. (Rafshanjani et al, 2014;Mondal et al, 2014). The ethanol extract showed the lowest mortality at all doses compared with those extracts, and the highest dose (1.131 mg cm -2 ) obtained 40% mortality at the end of the experiment (48 h) (Table 1).…”
Section: Toxicity Assaymentioning
confidence: 93%